Solid substrate fermentation (SSF) of rice husk using aspergillus niger - Nur Fathin, Binti Ruslan (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Rice husk is one of the highly potential lignocellulosic wastes that can be used as substrate for the production of cellulase via solid state fermentation. The present work was aimed to obtain cellulase from locally isolated Aspergillus niger cultured on rice husk via solid substrate fermentation (SSF) and also to determine its optimum conditions. Three parameters were studied which were initial moisture content of rice husk, pH and time of incubation. In this study, the optimum condition for cellulase production of solid substrate fermentation was recorded at 65% (v/w) initial moisture content, pH 4.0 and on the 6th day of incubation. The enzyme was extracted, incubated with FPase and assayed by using DNS method in order to determine the total amount of reducing sugar produced. The results from this work present the promising capability of rice husk as substrate for cellulase production by A. niger.